1977
DOI: 10.1111/j.1432-1033.1977.tb11770.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Erythrocyte Lactate Dehydrogenase by High Concentrations of Pyruvate. Evidence for the Competitive Substrate Inhibition

Abstract: The mechanism of the inhibitory effect of high concentrations of pyruvate on human erythrocyte lactate dehydrogenase has been studied by the use of a new parameter, A , defined as the difference between the reciprocals of initial reaction rates obtained from experimental measurements and hypothetical linear Lineweaver-Burk plots. This parameter served as a method for differentiating between the competitive and uncompetitive substrate inhibition. Results of this study indicate that pyruvate is a competitive sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The absence of linearity for SAV UM , SAV DEX , and SAV FIC (Fig. 1F) indicates that competitive binding of substrate to the active-site is not the cause of inhibition at high substrate concentrations (Wang, 1997). The markedly undulating curves, particularly for SAV UM (Fig.…”
Section: Kinetic Analysis Indicates Uncompetitive Substrate Inhibitiomentioning
confidence: 96%
See 2 more Smart Citations
“…The absence of linearity for SAV UM , SAV DEX , and SAV FIC (Fig. 1F) indicates that competitive binding of substrate to the active-site is not the cause of inhibition at high substrate concentrations (Wang, 1997). The markedly undulating curves, particularly for SAV UM (Fig.…”
Section: Kinetic Analysis Indicates Uncompetitive Substrate Inhibitiomentioning
confidence: 96%
“…The kinetics were further analyzed by the D method of Niday et al (1980) and Wang (1997). Lineweaver-Burk plots (Fig.…”
Section: Kinetic Analysis Indicates Uncompetitive Substrate Inhibitiomentioning
confidence: 99%
See 1 more Smart Citation
“…In order to increase the activity of 6-PGDH, and hence lower the simulated in i o steady-state concentration of 6- [87] showed that the allosteric and co-operative properties of PK are strongly influenced by pH and this suggested that the transition from R to T involves a deprotonation ; examination of the values that these workers obtained for L at different pH values shows that they are most closely matched if it is assumed that n l 1 (to the nearest integer) ; the pH-dependence of the inhibition of erythrocyte PK by iodoacetamide involves a group that has a pK a of 6.8 [88] ; it was assumed that this was the group that was involved in the R-to-T transition. [89] adjusted to 37 mC using the van 't Hoff equation ; d K eq l Lac NAD/(NADH Pyr) ; e k cat,f was calculated from the specific activity of the partially purified human erythrocyte enzyme (400 units/mg at pH 7.4, 37 mC ; [90]) ; the M r of the tetramer was taken to be 144 000 (see [90]) ; the specific activity of the forward reaction was found to be 4.7 times that of the reverse reaction [91] ; f the concentration of LDH in human erythrocytes, e o , was estimated from the measured human erythrocyte activity (66000 units/litre of erythrocytes, pH 7.6, 37 mC ; [62]) and the value of k cat,f . PG, the K m values of NADP + and 6-PG were decreased by a factor of 2, while the K m values for Ru5P and NADPH were increased by a factor of 2.…”
Section: Enzymes Of the Pppmentioning
confidence: 99%
“…The ternary formation has become better known as an E-NAD + -Pyr adduct complex [2][3][4][5]. Additional work promoted the idea of simple enzyme-pyruvate binary complexes and other inhibiting ternary complexes involving only cofactors [6,7]. Recently, the substrate binding has been examined with extremely small timescales to better understand the enzyme's intricate mechanics [8].…”
Section: Introductionmentioning
confidence: 99%